Analysis and network remodeling of a local water district in Kalibo using a hydraulic modeling program - Lachica, Daniel T.; Herrera, Eugene C. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
The main challenge in developing communities is the capacity of the water distribution network to meet the volume of water demanded by the concession within sufficient pressure. For the past years, the concessionaires of a local water district in Metro Kalibo endured intermittent water supply caused by the hydraulic instability of the distribution network. This have been brought by the rapid population growth, degrading of the pipe network and inapt expansion and development of the water distribution system. The aim of the study therefore is to evaluate the hydraulic performance of the current water distribution network and to recommend solutions to improving its performance. Using a hydraulic software (EPANET), the water distribution system of Kalibo was modeled to assess the hydraulics of the water distribution network, identify system components preventing the adequate supply of water, and recommend measures of improving service to the concession, in terms of volume and pressure. The hydraulic model was calibrated and validated using available pressure readings at different locations in the network. Simulation results of the present condition showed zero pressures occurring at junctions located in the towns of East Kalibo, Balete and Banga during peak demand periods. The zero pressures may have been caused by high head losses in small pipes of the system. A 2030 projected scenario is then developed and simulated to identify measures for improving the water distribution system to perform within minimum design pressures of 3 m. The distribution network is first modified by only adjusting the pipe diameters and pipe roughness only. The network is then improved by adding storage tanks only. In the last scenario, the water distribution system is modified by simultaneously adjusting the pipe diameters and roughness and adding storage tanks. Results show that simultaneously modifying the water distribution system is the better approach to providing the water distribution network flexibility for future expansion and the ability to supply water with the required pressures during peak demand periods. Hence, the study proposes increasing the sizes of small diameter pipes and adding tanks on specific areas to mitigate the zero nodal pressures during peak demand hours at critical areas. The suggested diameter change for the West Nautical Highway pipeline in Balete is an increase from 150 mm 10 200 mm or 250 mm diameters while the diameters of pipelines along Roxas Avenue. J. Cardinal Sin Avenue and Toting Reyes Street in Kalibo are recommended to be adjusted from 100 mm to 150 mm. Moreover, the study recommends the inclusion of four elevated tanks to act as buffer supply on critical areas during peak demand specifically on Barangay Tambak in New Washington, Barangay New Buswang in Kalibo, Barangay Tabayon in Balete and Barangay Cortez in Balete. Numerical modeling has been an essential tool in developing this study as it enabled the researcher to analyze the entire system and identify/simulate different alternative design solutions comprehensively. With the use of the model also, different algorithms and methodologies were performed while providing dynamic and quantitative results at the same time, thus providing an easy and convenient way of understanding the hydraulics of the system.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Water -- Distribution -- Philippines -- Kalibo; Hydraulic models